Returning home: forced conscription, reintegration, and mental health status of former abductees of the Lord's Resistance Army in northern Uganda - Vinck Patrick; Pham Phuong N; Stover Eric (BMC Psychiatry, 2009)
Abstract Background Since the late 1980s, the Lord's Resistance Army (LRA), a spiritualist rebel group in northern Uganda, has killed and mutilated thousands of civilians and abducted an estimated 52,000 to 75,000 people to serve as soldiers, porters, and sex slaves for its commanders. This study examines the types of violence to which former abductees have been exposed and the extent to which these acts have affected their psychological well-being. Methods This is a cross-sectional study of 2,875 individuals selected through a multi-stage stratified cluster sampling design conducted in 8 districts of northern Uganda. Multivariate logistic regressions were performed with symptoms for Post-traumatic Stress Disorder (PTSD) and depression as the main outcome measures. Results One-third of the respondents (33%) self-reported having experienced abduction (49% among the Acholi, the largest tribal group in northern Uganda). Over half (56%) of all the respondents and over two-thirds of those who experienced abduction met the criteria for symptoms of post-traumatic stress disorder (PTSD). Multivariate analysis shows that several factors increased the risk of former LRA abductees developing symptoms of PTSD. These factors included gender (females were more susceptible than males), being a member of the Acholi ethnic group, participating in or witnessing a cumulative number of traumatic events, and encountering difficulties re-integrating into communities after abduction. Factors associated with increased risk of meeting criteria for symptoms of depression included older age of males at the time of abduction, lower score on social relationship scale, high incidence of general traumatic event exposure, high incidence of forced acts of violence, and problems reintegrating into communities after abduction. Conclusion Abduction and forced conscription of civilians has affected the psychological well-being of a significant number of northern Ugandans. The sources of psychological trauma are multiple, ranging from witnessing to being forced to commit violent acts, and compounded by prolonged exposure to violence, often for months or years. Community-based mental health care services and reintegration programs are needed to facilitate the reintegration of former abductees back into their communities.